Evaluation of the effect of oral omeprazole on canine cerebrospinal fluid production: A pilot study. (March 2016) - Girod, M.; Allerton, F.; Gommeren, K.; Tutunaru, A.C.; de Marchin, J.; Van Soens, I.; Ramery, E.; Peeters, D.
Highlights: The effect of oral administration of omeprazole on cerebrospinal fluid (CSF) flow was assessed in dogs. The albumin quotient (QAlb) was used as a marker of CSF flow. There was no change in QAlb after 14 days of oral administration of omeprazole. There was no evidence of an effect of omeprazole on CSF production in healthy dogs. Abstract: Administration of omeprazole by ventriculo-cisternal perfusion or intravenously has been shown to decrease cerebrospinal fluid (CSF) production in dogs and rabbits. Oral omeprazole has consequently been recommended to reduce CSF production in dogs with conditions in which clinical signs may be attributable to an accumulation of CSF in the central nervous system (e.g. hydrocephalus, syringomyelia). The albumin quotient (QAlb), the ratio between CSF and serum albumin concentration, has been proposed as a reliable means to evaluate CSF production; decreasing CSF production should cause an increase in QAlb. The aims of this study were to assess the effect of oral administration of omeprazole on QAlb in dogs and to compare two methods to assess CSF albumin concentration. Fifteen healthy Beagle dogs received omeprazole (1.2 mg/kg/day) orally for 14 days; CSF and blood were obtained before and after treatment. CSF albumin concentrations were evaluated by nephelometry and high-resolution protein electrophoresis. Regardless of the method used for measuring albumin, QAlb did not change significantly following oral omeprazole administration, suggesting that CSF production in healthy dogs may not be affected by chronic oral therapy with omeprazole.